PERBANDINGAN ANTENA MIKROSTRIP ARRAY DUAL BAND DENGAN PENCATUAN MICROSTRIP LINE DAN ELECTROMAGNETICALLY COUPLED (EMC) - Citra Andrieyani; Bambang Sumajudin; Trasma Yunita (TEKTRIKA, 2020)
Single microstrip antenna has the characteristics of narrow bandwidth and small gain. This paper discusses the design of a microstrip array antenna that works at two working frequencies, namely 2.4 GHz and 5 GHz for WiFi. The method used to obtain dual band frequencies is by adding slots on the side of the patch. The results obtained are the 4-element microstrip array antenna with feed line supply has better results when applied to WiFi. This feed line antenna has a bandwidth of 75 MHz - 184.4 MHz in accordance with IEEE 802.11n standards and has a gain of 4.321 dBi. Whereas the EMC supply has a large gain of 11.54 dBi but the bandwidth obtained is very narrow, namely 27.5 MHz.